DEVELOPING ANALYTICAL THINKING ABILITY OF MATHAYOMSUKSA 4 STUDENTS IN BIOLOGICAL SCIENCE USING PHENOMENON – BASED LEARNING - Tassaniyom, Anubes; Chookhampaeng, Sumalee (Journal of MCU Nakhondhat, 2020)
This classroom action research aimed to develop 10th graders’ analytical thinking ability by using phenomenon – based learning to meet the criteria of 75 per cent. The participants were 15 students from a total of 29 students in a classroom who studied Biological Science course at Phadungnaree School, Mahasarakham Province, the academic year 2019. By developing the purpose of this research, the researchers collected data from two instruments. Firstly, the 4 multiple – choice analysis test, not based on content, divided into 3 components, 10 items each, for a total of 30 items, takes 1 hour. Secondly, the student interview consisting of 3 aspects: the ability in Analytical thinking in the teaching and learning activities and the teacher’ teaching. Then analyze the data with basic statistics the results of the study revealed that 75% of the students who learned through the phenomenon – based learning management plan had the analytical thinking ability through the criteria that set by the researcher. There were 7 students passing the criteria specified by the researcher in the first cycle and found that the target group of 8 people did not meet the criteria due to the duration of the activities. In the 2nd operation cycle, there were 12 students who passed the specified criteria from the researcher, and there are still 3 target group students who do not yet pass due to lack of motivation in teaching and learning activities. The operation cycle 3, it was found that all students passed the criteria set by the researcher due to the time and familiarity in teaching and learning activities, enabling them to develop their ability to think analytically.